Entrepreneurship Development Programme and Job Creation in Awka, Anambra State Nigeria - Ojukwu, Henry; Nwankwo, Catherine Nkechi; OKPARA, Elizabeth Obianuju (International Journal of Entrepreneurship and Business Management, 2024)
The problem of unemployment has remained a reoccurring issues in Awka, Anambra State and Nigeria as a whole. In bid to this problem, the study focused on the effect of entrepreneurship on job creation in Awka, Anambra State. The study was anchored on Human Capital Theory by Becker (2002). Descriptive survey research design was adopted for the study and complete enumeration was used to determine the sample size of 270 which also is the population size of the study. Data were collected with the aid of structured questionnaire while bio data were presented using simple frequency and percentage tables. Data were analyzed using arithmetic mean and hypotheses were tested using Simple Regression analysis with the aid of Statistical Packages for Social Sciences (SPSS version 27). Findings revealed that there is significant effect of entrepreneurship development on job creation in Awka, Anambra State, Nigeria by indicating positive effect of entrepreneurship education on job creation, secondly, positive relationship between entrepreneurship skill training and job creation; and lastly, positive effect of entrepreneurship continuity on job creation. The study concluded that entrepreneurship development significantly contributes to job creation as indicators of entrepreneurship development such as entrepreneurship education, entrepreneurship skill training and entrepreneurship continuity promotes self-employment and generate employment for others. The study therefore, recommended that both government and non-government organizations should focus on entrepreneurship developmental programmes as solution to unemployment situation in Awka, Anambra State.